Advances in intensity-modulated radiotherapy delivery. - Fenwick, J; Riley, S; Scott, A (2008)
Fixed-field intensity-modulated treatments, delivered by conventional linac-plus-multileaf systems, have rapidly become the most common form of IMRT. Several innovative alternative IMRT options are also now available, including tomotherapy, CyberKnife and jaws-only linacs. These innovative approaches have divergent rationales. Jaws-only IMRT is being developed because it allows treatments to be delivered using conventional linacs without expensive multileaf collimators and not because it improves dose distributions. On the other hand, tomotherapy and CyberKnife systems have different geometric degrees of freedom, beam sizes and modulation techniques than those of conventional linacs, which may enable these innovative systems to deliver superior dose distributions to some treatment sites. Because conventional linacs are themselves finely honed machines, enhancement of one aspect of machine performance is sometimes accompanied by diminution of another. For example, tomotherapy systems possess an enhanced rotational IMRT capability but currently can only deliver coplanar radiation beams. Thus the various delivery systems may prove optimal for different types of treatments, specific machine designs excelling for specific disease sites. In practice, of course, IMRT delivery systems will be distinguished not just by the quality of the dose distributions they deliver but also by factors not discussed in this chapter, such as the efficiency of their treatment process, the integration of on-board imaging into that process, and their ability to measure, minimise and compensate for the effects of respiratory motion, a major detriment to accurate IMRT delivery.